Edukasi Fisioterapi Komunitas Pemberian Latihan Untuk Penanganan Awal Cedera Pergelangan Kaki Pada SiswaMadrasah Terpadu Daqumi – MTs Darul Qur’an - Dewi Hapsari; Safun Rahmanto; Lisna Tanjung (Rena Cipta Mandiri, 2024)
Ankle sprain is one of the most common injuries that occur in schools during sports activities. Injuries can occur at the beginning of sports activities or during sports, this can occur due to lack of warm-up, inadequate infrastructure, low flexibility, uncontrolled movement, and also due to fatigue. The impacts that can occur are pain, swelling, weakness and limited range of motion of the ankle joints. The prevalence of ankle injuries in East Java is 30.5% caused by sports injuries and around 5.83% of total injuries occur around schools and their environments. Sports activities at school such as basketball, martial arts, running and other sports activities that can result in ankle sprains. Objective: This counseling aims to provide knowledge of handling and training for injuries independently to MTS Darul Qur'an students. Method: The method used is to provide physiotherapy counseling that focuses on handling and training ankle injuries with posters and leaflets. The evaluation results obtained before and after answering the quiz from the presentation of the material, can be concluded that the participants have understood the material that has been presented and have a better understanding of ankle sprains.